Effect of supportive counseling on pregnancy-specific stress, general stress, and prenatal health behaviors: A multicenter randomized controlled trial. Issue 11 (November 2020) - Esfandiari, Maria; Faramarzi, Mahbobeh; Nasiri-Amiri, Fatemeh; Parsian, Hadi; Chehrazi, Mohammad; Pasha, Hajar; Omidvar, Shabnam; Gholinia, Hemmat
Highlights: This is first RCT of effect of supportive counselling on improvement of prenatal care. Supportive counselling decreased general anxiety and pregnancy stress. Healthy behaviors improved in supportive counselling group more than usual care. 6 weeks of group supportive counselling diminished unhealthy behaviours. We propose supportive counselling as an adjunctive care for improvement of prenatal care. Abstract: Objective: The aim of this study was to investigate the effects of group supportive counseling (SC) on pregnancy-specific stress, general stress, and healthy behavior of pregnant women. Methods: This randomized controlled trial study was conducted on 80 pregnant women in two groups; SC for six sessions, once a week for two hours (n = 40), and antenatal usual care (AUC) (n = 40). All Participants completed questionnaires measuring pregnancy-specific stress, state anxiety, prenatal health behaviors, perceived stress, and provided a saliva sample for measurement of cortisol at pre-intervention and 6-week post-intervention. Results: The post-intervention results indicated that the outcome scores decreased more significantly in group SC than in the AUC for total NuPDQ, for state-anxiety, for PSS-14, and for unhealthy behaviors with a large effect size. Also, healthy behaviors were promoted more significantly in SC group than in AUC. However, salivary cortisol levels did not differ between group SC and AUC groups. Conclusion: Group supportive counselling can promote pregnancy stress and healthy behaviors. Practice Implications: Addition of supportive counseling to prenatal usual care may be suggested for pregnant women with any gestational age who seek methods for improving pregnancy stress and healthy behaviors.